Analisis Struktur Vegetasi dan Riap Tanaman Ampupu (Eucalyptus urophylla S.T Blake) di Kawasan Hutan Tanaman Bu’at, Kabupaten Timor Tengah Selatan - Hilda Audreya Consita Soares; Wilhelmina Seran; Nixon Rammang (Wana Lestari, 2024)
This research has been carried out in the Bu'at Research Forest Area which is included in the Bu'at KHDTK Area, South Mollo District, South Central Timor Regency, East Nusa Tenggara Province. This research has been carried out in July 2023. This study aims to determine the vegetation structure of Ampupu plants (Eucalyptus urophylla S.T Blake) and riap Ampupu plants (Eucalyptus urophylla S.T Blake) in the Bu'at Plantation Forest Area. The method used in this study is quantitative method. The results of the research obtained through the plot method. The data in this study is in the form of seedling to tree level analysis in plantation forests and riap data of Ampupu plants (Eucalyptus urophylla S.T Blake). The results of this study were the average diameter, height and volume of Ampupu plants in plots 1 to 38 when the plants were 41 (forty one) years old respectively amounted to 39.08 cm, 1528 cm and 22.57 m3. The average riap diameter, height and volume of Ampupu type plants in plots 1 to 38 when plants are 41 (forty one) years old are respectively 0.94 cm / plant / year, 41.72 cm / year / plant and 0.556 m3 / plant / year.